Comunidade de fungos filamentosos em um fragmento de Floresta Estacional Semidecidua no Parque Estadual das Sete Passagens, Miguel Calmon, Bahia - Marques, Marcos Fabio Oliveira (2012)
The importance of the filamentous fungi does not concern only to the role they play in the ecologic balance as decomposers and regulators of phytopathogenics, but also for the secondary enzymatic and metabolic potential they can produce and they are also used in the food and pharmaceutical industry. However, knowledge about the diversity and ecological aspects of filamentous leaf litter, aerial litter and airborne fungus in Brazil is still incipient.The filamentous fungi of semideciduous seasonal forest in the “Parque Estadual das Sete Passagens” (PESP), Miguel Calmon, Bahia, were studied in order to know the composition, richness, diversity and abundance of fungi related to environmental area factors. For fungal leaf litter and aerial litter samples were collected in a period between Oct/2009 Sep/2010. Eight plots were sampled and materials with litter and litter air were collected. The material was washed in tap water and placed in moist chambers. Permanent slides were made from the material and later species were identified. The airborne fungi collections occurred between October/2009 and March/2010, they were exposed to four Petri dishes containing agar Sabourand, DG-18, CMA and Malt in four hours 8h, 12h, 20h 16 h during the dry and rainy seasons. The plates were incubated and then the colony forming unities (CFU) were counted and identified. The thesis is divided into chapters and the following results were obtained: (I) it was observed the richness of 95 taxons associated with leaf litter (62) and air litter (55). The cluster analysis showed variation in species composition among the sites. The principal coordinates analysis did not detect formation of distinct groups of litter and litter air. The leaves were the most colonized substrate. (II) The ground litter was richer with 37 (taxons) and 35 aerial litter. There was a large diversity of sampling points for the ground litter. The similarity among litter was 69% and the frequency of occurrence was sporadic for most fungi and (III) 26 taxons of airborne fungi were identified, distributed in 15 genera. Cladosporium cladosporioides and Penicillium sp. were the most abundant taxon. The richness and diversity of species was greater for 12h. The studies contribute to understanding the interaction between fungi - litter and aerial litter, as well as the dynamics of airborne fungi in the atmosphere in areas of semideciduous seasonal forest.